PHYSICAL ACTIVITY OF STUDENTS WITH DISABILITIES – SELECTED ISSUES - Tomporowska, J.; Grygus, I.; Levandowska, L. (Rehabilitation and Recreation, 2023)
The health of the population, and above all children and youth, is a fundamental value in the development strategies of most countries in the world. The World Health Organization, defining its main goals for Europe in the Health 2020 program, points to the promotion of health and the reduction of inequalities in health. However, in order to define specific objectives in individual countries, it is necessary to thoroughly diagnose the existing situation, the main threats, and to define target groups for preventive and intervention activities. A very complex element is also the assessment of inequalities in health, and above all their psychosocial causes. The activity of an individual is one of the main factors influencing the development of its mental processes and properties, it is the opposition of the active state of the body to states of passivity, immobility, lack of reaction. Activity is both a concrete act of action and the ability to actively regulate relations with the environment, according to human needs, goals and ideals. Therefore, one of the most important tasks of a modern school is the activation of students, giving them the opportunity to develop various forms of their activity, and at the same time enabling the individual to fully meet their mental, physical and social needs. At school, it can manifest itself in the cognitive, physical, productive, social, cultural and artistic activities. In the process of educating students with disabilities, particular importance is attached to physical activity, which not only serves to maintain their health and general fitness so that they can function as fully as possible in social life, but is also a form of physical rehabilitation, an element of psychotherapy. It manifests itself through various forms of physical activity of utilitarian importance (walking, running, physical work) in connection with professional, home or recreational activities (walking, sports, tourism, dancing, physical games, physical exercises). Physical activity understood as a consciously directed action is also a factor directly affecting the body's activities and enabling its adaptation, especially to long-term physical effort, and preventing the development of many civilization diseases, constituting a research challenge for many fields and scientific disciplines.